Safe exercise prescription for children and adolescents - Alleyne, Julia MK (Pulsus Group Inc, 1998)
This article provides practical advice on healthy exercise prescription for children. There is growing scientific evidence about the abilities and limits of child athletes in both recreational and competitive environments. As exercise becomes essential for the prevention of illness and maintenance of health, the counselling for an exercise prescription requires enhanced knowledge. The latest recommendations on safe strength, resistance and weight training are presented in a concise format for office use.